2023
DOI: 10.1111/jsr.13944
|View full text |Cite
|
Sign up to set email alerts
|

Mild‐to‐moderate obstructive sleep apnea and mortality risk in a general population sample: The modifying effect of age and cardiovascular/cerebrovascular comorbidity

Abstract: SummaryAbout 5.4%–45.7% of the general population has mild‐to‐moderate obstructive sleep apnea (mmOSA), which is highly comorbid with cardiovascular and/or cerebrovascular diseases (CBVD). We examined the association between mmOSA and all‐cause mortality and the modifying effect of age and CBVD. A total of 1681 adults 20–88 years old from the Penn State Adult Cohort (PSAC) (41.9% male) were followed up for 20.1 ± 6.2 years for all‐cause mortality. Mild and moderate OSA were defined as an apnea/hypopnea index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The relationship between OSA and cerebral infarction remains controversial. Studies have suggested that OSA can lead to an adverse prognosis in cerebral infarction, impair brain function, exacerbate cognitive dysfunction, and increase mortality risk (30)(31)(32)(33). The main mechanisms underlying these adverse outcomes include chronic intermittent hypoxia, sympathetic activation, changes in cerebral blood flow, oxidative stress, systemic inflammation, hypercoagulability, and endothelial dysfunction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OSA and cerebral infarction remains controversial. Studies have suggested that OSA can lead to an adverse prognosis in cerebral infarction, impair brain function, exacerbate cognitive dysfunction, and increase mortality risk (30)(31)(32)(33). The main mechanisms underlying these adverse outcomes include chronic intermittent hypoxia, sympathetic activation, changes in cerebral blood flow, oxidative stress, systemic inflammation, hypercoagulability, and endothelial dysfunction (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…CIH increases the gain of the carotid body response to hypoxia, which seems to be a major cause for the multiple comorbidities of OSA ( Iturriaga, 2023 ; Prabhakar et al, 2023 ). These OSA-related comorbidities ( Pack, 2023 ) include an increase in mortality ( Vgontzas et al, 2023 ) and cancer risk ( Sánchez-de-la-Torre et al, 2023 ), increased arousal and sleep fragmentation ( Horner, 2023 ), increased sympathetic drive leading to cardiovascular disease, metabolic syndromes such as obesity and diabetes ( Kurnool et al, 2023 ), renal disease, asthma ( Bonsignore et al, 2019 ), and decreased cognition ( Brockmann and Gozal, 2022 ). OSA is also commonly associated with altered and disordered swallow function, clinically known as dysphagia ( Pizzorni et al, 2021 ; Schindler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…CIH increases the gain of the carotid body (CB) response to hypoxia which seems to be a major cause for the multiple comorbidities of OSA (Iturriaga, 2023;Prabhakar et al, 2023). These OSA-related comorbidities (Pack, 2023) include an increase in mortality (Vgontzas et al, 2023) and cancer risk (Sánchez-de-la-Torre et al, 2023), increased arousal and sleep fragmentation (Horner, 2023), increased sympathetic drive leading to cardiovascular disease; metabolic syndromes such as obesity and diabetes (Kurnool et al, 2023), renal disease, asthma, (Bonsignore et al, 2019), and decreased cognition (Brockmann & Gozal, 2022). OSA is also commonly associated with dysphagia, disordered swallow function (Pizzorni et al, 2021;Schindler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%